IMPLEMENTASI KEPUTUSAN GUBERNUR SUMATERA SELATAN NOMOR. 201/KPTS/BPKAD/2017 TENTANG PENERAPAN PPK-BLUD BPSDMD PROVINSI SUMATERA SELATAN - Kabul Aman (Jurnal Good Governance, 2018)
The Implementation of PPK-BLUD is an exception in financial management in general which provides flexibility in the form of freedom to implement sound business practices to improve service to the community. Exceptions given are intended to improve service quality and performance productivity which are non profit oriented. So that not all regional apparatus or work units of regional apparatus can implement PPK-BLUD, but only regional device organizations or work units of regional apparatus whose main tasks and functions provide services directly to the community or in other terms called Quasi Public Goods, namely regional apparatus in its operations some of it is financed from the Regional Revenue and Expenditure Budget, partly from the results of the services provided, however, its nature is not solely for profit. The application of PPK- BLUD in the Regional Human Resource Development Agency of the Province of South Sumatra is stipulated by Governor Decree Number 201 / KPTS / BPKAD / 2017 dated March 17, 2017 with Full BLUD status. The purpose of implementing PPK BLUD is 1) Improving the quality of public services in this case education and training services; 2) Improving efficiency and Financial Performance; 3,) Increasing benefits for Stakeholders. After implementing PPK-BLUD BPSDMD, South Sumatra Province gets funding sources in the form of services from the results of cooperation with the regency / city government in Sumatra, South Sumatra, vertical agencies in the region, as well as ministries including the Ministry of Human Rights, Kemenrisdikti, Supreme Court and provincial/district governments/cities and other institutions in implementing cooperation in the implementation of education and training.Keywords: PPK-BLUD; Performance; Development